Analysis of successful outcome in patients undergoing homologous intrauterine insemination - Marimuthu, Kavitha; Dakshnamurthy, Padmalatha; Kailash, Udhayarani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Intrauterine insemination (IUI) is a cost-effective, non-invasive and its success depends on the various factors. The factors associated with the success of IUI and its literature is least available in the Indian context. Objectives were to analyze the outcome of patients undergoing homologous IUI in terms of pregnancy rates (clinical pregnancy) and its predictors for the outcomes. Methods: This is a prospective observational study among 200 couples with infertility undergoing therapeutic homologous IUI in a tertiary care centre. Among the study participants, undergoing IUI, after obtaining the informed written consent, the data related to the outcomes and associated factors were collected through a pre structured Questionnaire. Results: Among the study participants who undergone the procedure, 40 (20%) become positive for pregnancy. Of the 40 positive, 30 (15%) delivered normal babies and 7 (14%) went for spontaneous abortions and 1 (0.5%) went for D and C. Type of infertility, drug for induction of ovulation, age in years, years of marriage, day of ovulation, no. of ovulation induction and were not statistically significant with the outcomes. Endometrial thickness, greatest dimension of follicular size, increased total sperm count, percentage of motility, post wash count and post wash motility were significantly associated with the positive outcomes. Conclusions: Since the success rate of the IUI is comparable to the other studies reported, and the procedure is relatively cheaper, the same can be recommended as the simple and cost effective first line management of certain specific indications of the infertility.